2008
DOI: 10.1177/1548051808326596
|View full text |Cite
|
Sign up to set email alerts
|

Authentic Leadership and Positive Psychological Capital

Abstract: This study investigates the relationship between authentic leadership, trust, positive psychological capital (PsyCap), and performance at the group level of analysis. Data were collected from a small Midwestern chain of retail clothing stores, a context in which the needs for both authentic leadership and a positive sales staff are integral to the firm's performance. Constructs were aggregated to the store (group) level to test relationships between perceptions of authentic leadership, trust in management, pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
91
0
7

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 386 publications
(124 citation statements)
references
References 44 publications
3
91
0
7
Order By: Relevance
“…With its roots in positive psychology, authentic leadership has been said to instill hope and optimism (Avolio et al, 2004), positive health (Macik-Frey et al, 2009), and eudemonic well-being (Ilies et al, 2005). While empirical findings relate authentic leadership positively to psychological capital (Clapp-Smith et al, 2009;Rego et al, 2012), positive working relations (Wang et al, 2014), well-being (Toor and Ofori, 2009), empowerment (Wong and Laschinger, 2013), and negatively to adverse health outcomes (e.g., burnout, stress; Laschinger and Fida, 2014a;Laschinger and Fida, 2014b;Laschinger et al, 2012;Rahimnia and Sharifirad, 2014), there is no research that links it to leaders' or followers' work-life balance. In the face of organizational initiatives and government policies for employee well-being (Fleetwood, 2007;Morganson et al, 2014;Munn, 2013;Wang and Verma, 2012), and a range of positive outcomes that work-life balance holds (e.g., job satisfaction, life satisfaction, mental health; Haar et al, 2014; career advancement potential; Lyness and Judiesch, 2008), we believe that analyzing this relationship is an important endeavor.…”
Section: Crossover Of Work-life Balance Perceptionsmentioning
confidence: 99%
“…With its roots in positive psychology, authentic leadership has been said to instill hope and optimism (Avolio et al, 2004), positive health (Macik-Frey et al, 2009), and eudemonic well-being (Ilies et al, 2005). While empirical findings relate authentic leadership positively to psychological capital (Clapp-Smith et al, 2009;Rego et al, 2012), positive working relations (Wang et al, 2014), well-being (Toor and Ofori, 2009), empowerment (Wong and Laschinger, 2013), and negatively to adverse health outcomes (e.g., burnout, stress; Laschinger and Fida, 2014a;Laschinger and Fida, 2014b;Laschinger et al, 2012;Rahimnia and Sharifirad, 2014), there is no research that links it to leaders' or followers' work-life balance. In the face of organizational initiatives and government policies for employee well-being (Fleetwood, 2007;Morganson et al, 2014;Munn, 2013;Wang and Verma, 2012), and a range of positive outcomes that work-life balance holds (e.g., job satisfaction, life satisfaction, mental health; Haar et al, 2014; career advancement potential; Lyness and Judiesch, 2008), we believe that analyzing this relationship is an important endeavor.…”
Section: Crossover Of Work-life Balance Perceptionsmentioning
confidence: 99%
“…Recientes estudios realizados en diversos países y utilizando diferentes grupos ocupacionales, apoyan la existencia de una relación positiva entre el capital psicológico positivo y otras variables psicosociales y organizacionales tales como el liderazgo, la confianza, la creatividad, y el rendimiento, entre otras (Clapp-Smith, Vogelgesang y Avey, 2009;Rego, Sousa, Marqués y Pina e Cunha, 2012). Por ejemplo, en un estudio longitudinal de Clapp-Smith, et al (2009) que incluyó 89 empleados de 26 pequeñas tiendas de ropa en Estados Unidos, se investigó la relación entre el liderazgo, la confianza, el capital psicológico positivo y el rendimiento utilizando un nivel de análisis grupal.…”
Section: Capital Psicológico Positivounclassified
“…Por ejemplo, en un estudio longitudinal de Clapp-Smith, et al (2009) que incluyó 89 empleados de 26 pequeñas tiendas de ropa en Estados Unidos, se investigó la relación entre el liderazgo, la confianza, el capital psicológico positivo y el rendimiento utilizando un nivel de análisis grupal. Se encontró que el capital psicológico positivo y el rendimiento estaban mediados por la confianza que, a su vez, también mediaba parcialmente la relación entre el liderazgo auténtico y el rendimiento.…”
Section: Capital Psicológico Positivounclassified
See 1 more Smart Citation
“…Scholars have maintained that various individual traits such as transparency, integrity and self-discipline are integral to authentic leadership (Ilies, Morgeson, & Nahrgang, 2005;Avolio, Gardner, Walumbwa, Luthans & May, 2004). Numerous studies focusing on authentic leadership have indicated that it is a major determinant of several positive organizational outcomes; for instance, employee creativity (Cerne, Jaklic & Škerlavaj, 2013), 'psychological capital' of followers (Clapp-smith, Vogelgesang, & Avey, 2009), employee satisfaction (Walumwa et al, 2008), follower ethical decision-making (Cianci, Hannah, Roberts & Tsakumis, 2014), organizational citizenship behaviour (Walumwa et al, 2008) and employee well-being (Rahimnia & Sharifirad, 2015;Nelson et al, 2014).…”
Section: Background and Objectivesmentioning
confidence: 99%